Gradient of extrajunctional acetylcholine receptors early after denervation of mammalian muscle - Levitt-Gilmour, TA (J Neurosci, 1986)
After denervation, the number of acetylcholine receptors (AChR) found within the endplate band of skeletal muscle increases transiently by about twofold. In this study, we used EM autoradiography to show that this increased endplate band label is not due to an elevated site density of receptors at the junctional folds. Rather, AChR site density within 500 microns of the endplate was found to be 4 X higher than in non-endplate areas defined as greater than 2 mm from the endplate. This nonuniform distribution of extrajunctional AChR early after denervation could represent a transient gradient,similar to that reported shortly after innervation during development.